USING THE NATURAL AND RECREATIONAL POTENTIAL OF THE REGION IN PHYSICAL AND HEALTH ACTIVITIES - Kuznietsova, O. T.; Kucher, T. V.; Khoma, O. V. (Rehabilitation and Recreation, 2025)
Due to its physical-geographical features, climate conditions, natural-resource potential, and socioeconomic conditions, Rivne Oblast belongs to regions that have favorable preconditions for tourism and recreation development. Almost all types of recreation are developed in the region: from sanatorium and resort treatment to leisure activities, and there are also favorable conditions for year-round development of various types of wellness physical culture. Therefore, it is relevant to characterize the natural resources of the Rivne region, which will help identify the prerequisites for recreational activities and determine measures for their effective use. The purpose – to reveal the use of the region’s natural and recreational potential in wellness activities using Rivne as an example. Research methods. To achieve the outlined goal, the following research methods were used: analytical (study and analysis of regulatory, scientific, and methodological literature on this issue, Internet resources), synthetic (comparison, systematization, generalization of materials). Results. A special value of the Rivne region is its unique natural environment. With the expansion of types and forms of physical education and recreation, it can be argued that the territory of the Rivne region has the potential to organize recreational activities and tourism. Recreational and tourist potential is the total productivity of explored natural resources and cultural values of the territory, which can be used for recreational purposes: for health improvement, recreation, and tourism. The main goal of the social project “Active Parks – Locations of Healthy Ukraine” is to involve people in systematic health training aimed at developing the basic motor abilities of a person. In order to implement the project within the framework of the educational process, the prospect of filling parks with activities was considered. The methodology for conducting physical education and recreation activities in the recreational zones of the city is presented: educational and health training and quest. Conclusions. The conducted research demonstrated the importance of using the natural and recreational potential of the region in physical culture and health activities. In modern conditions, knowledge of the natural resources of the Rivne region and their characteristics contribute to the development of new forms and methods of conducting educational activities.